Inflammatory cytokines are associated to lower glomerular filtration rate in patients with hypertensive crisis - Andrade, Days O.; Aguiar, Franciana L.; Mansor, Ana Luiza P.; Valente, Flavia M.; Souza, Doroteia R. S.; Lopes, Valquiria da Silva; Fernandes, Leticia B.; Godoy, Moacir F.; Yugar-Toledo, Juan C.; Cosenso-Martin, Luciana N.; Vilela-Martin, Jose F. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Hypertension and kidney function are closely related. However, there are few studies on renal function during acute elevation of blood pressure (BP), denominated hypertensive crisis (HC). Objectives To evaluate the relationship between renal function and inflammatory cytokines in HC, subdivided into hypertensive urgency (HUrg) and emergency (HEmerg). Materials and methods This cross-sectional study was carried out in 74 normotensive (NT) and 74 controlled hypertensive individuals (ContrHT) followed up in outpatient care. Additionally, 78 subjects with hypertensive emergency (HEmerg) and 50 in hypertensive urgency (HUrg), attended in emergency room, were also evaluated. Hypertensive crisis was classified into HEmerg, defined by systolic blood pressure (BP) ≥ 180 mmHg and/or diastolic BP ≥ 120 mmHg in presence of target-organ damage (TOD), and HypUrg, clinical situation with BP elevation without TOD. The glomerular filtration rate (eGFR) was estimated, and cytokine levels were measured. Statistical analysis was performed using the Kruskal-Wallis or Mann-Whitney test and Spearman’s correlation, with significant differences p-value < 0.05. Results The median age was 53.5 years in the NT group (52 female), 61 years in the ContrHT group (52 female), and 62.5 years in the HC group (63 female) (p-value < 0.0001). The median BP was 118.5/75 mmHg for NT, 113.5/71 for ContrHT, and 198.5/120 mmHg for HC, respectively (p-value < 0.0001 among groups). BP and heart rate levels were significantly higher in the HC group compared to the NT and ContrHT groups (P < 0.001 for all). The eGFR was significantly lower in HC group compared to the NT and ContrHT groups. The cytokine levels were higher in the HEmerg and HUrg groups compared to ContrHT group (P < 0.0001, except for IL-1β in HUrg vs. ContrHT), without difference between the acute elevation of BP groups. Thus, all cytokines were significantly elevated in patients with HC compared to the control groups (NT and ContrHT). There was a negative correlation between eGFR and the cytokines (IL-1β, IL-6, IL-8, IL-10, and TNF-α) in the HC group. Conclusion Elevated inflammatory cytokines are associated with reduced eGFR in individuals with HC compared to control groups, suggesting that the inflammatory process participates in the pathogenesis of acute elevations of BP.